Maintenance chemotherapy in advanced ovarian cancer: the US experience. (1st February 2008) - Markman, M.
Abstract : The somewhat controversial results of a Southwest Oncology Group/Gynecologic Oncology Group phase 3 randomized trial have revealed that a maintenance strategy consisting of 12 cycles of single-agent paclitaxel (175 mg/m 2 over 3 h every 28 days), delivered to women with advanced ovarian cancer who have achieved a clinically defined complete response to primary platinum–paclitaxel chemotherapy, significantly improves progression-free survival compared to delivery of three cycles of the same treatment regimen. While it is not possible to provide a definitive statement regarding the impact of this management approach on overall survival, in an exploratory analysis, patients who initiated this study with a baseline CA-125 level ≤10 units/mL and were treated with the 12-cycle maintenance program experienced a statistically significant improvement in survival. An ongoing Gynecologic Oncology Group trial in the United States will hopefully provide a definitive answer to the question of the impact of this novel strategy on outcome in ovarian cancer.